STRATEGIC ALIGNMENT IN THE BRAZILIAN AUTOMOTIVE CHAIN - Martins, Ricardo Silveira (2012)
The research objective is verifying the strategic alignment of supply practices between automakers and suppliers in the Brazilian automotive supply chains. It makes an exploratory-descriptive study of objectives, using quantitative/qualitative procedures and inductive reasoning. The concept used for analyzing the alignment of practices was based on Vachon et al. (2009). The main conclusion of this study is that suppliers and automakers seem to align their supply strategy, giving support to a desirable situation of single chain project. The subsidiary conclusion is the lack of relationship between intensity of the link and misalignment in these companies. The main contributions are the analysis of the relationship established in tiers that are the furthest removed from the focal companies; identification of practices that support the expansion of a new model of arrangements implemented by automakers in Brazil; and understanding of the processes that companies have adopted in order to manage their supply chains and the implications of these activities for the competitiveness of both the company and the supply chain as a whole.